Active layer thermal regime in two climatically contrasted sites of the Antarctic Peninsula region - Hrbáček, F. (2017)
Permafrost controls geomorphic processes in ice-free areas of the Antarctic Peninsula (AP) region. Future climate trends will promote significant changes of the active layer regime and permafrost distribution, and therefore a better characterization of present-day state is needed. With this purpose, this research focuses on Ulu Peninsula (James Ross Island) and Byers Peninsula (Livingston Island), located in the area of continuous and discontinuous permafrost in the eastern and western sides of the AP, respectively. Air and ground temperatures in as low as 80 cm below surface of the ground were monitored between January and December 2014. There is a high correlation between air temperatures on both sites (r=0.74). The mean annual temperature in Ulu Peninsula was -7.9 ºC, while in Byers Peninsula was -2.6 ºC. The lower air temperatures in Ulu Peninsula are also reflected in ground temperatures, which were between 4.9 (5 cm) and 5.9 ºC (75/80 cm) lower. The maximum active layer thickness observed during the study period was 52 cm in Ulu Peninsula and 85 cm in Byers Peninsula. Besides climate, soil characteristics, topography and snow cover are the main factors controlling the ground thermal regime in both areas.